Influence of lignosulfonic acids on the formation of magnetoactive compound in the redox reaction of iron(II) with chromate-anion - Yu. Kuzyakov, Nikolay; A. Veshnyakov, Viacheslav; G. Khabarov, Yuriy; V. Pankina, Galina (International Journal of Engineering and Technology, 2018)
Chromium and its compounds are widely used in various industries. Wastewater from industrial enterprises using chromium compounds are subject to complete disposal at treatment facilities. The possibility of synthesizing a magnetoactive compound by oxidizing part of Fe(II) cations with chromate-anions in the presence of lignosulfonates was investigated. The magnetic activity was measured on Gouy balance, magnetic characteristics were determined by the magnetic granulometry method. It has been shown that the interaction of Fe(II) cations with chromate-anions passes with the formation of an water soluble intermediate without redox transformations at pH 3.4. Using method of the isomolar series, it was determined that the ratio of chromate-ions and Fe(II) cations in the intermediate is 1:2.33. The intermediate solution is stable for a long time. Synthesized magnetoactive compound samples are ferrimagnets. The use of lignosulfonate and the synthesis with heating can achieve a higher magnetic activity of magnetoactive compound. The optimal lignosulfonate consumption is 0.7 g/g Fe.Â Â